Study of biochemical parameters along with correlation of Lipid profile and Vitamin D in obese and non-obese subjects - Borgaonkar, Kavindra; Patil, Ranjit (Panacea journal of medical sciences, 2024)
Background: Vitamin D deficiency can impose significant development of cardiovascular diseases along with the cardiovascular risk factors such as obesity, diabetes, hypertension and dyslipidemia. In this backdrop, the present study was carried to evaluate the association between 25(OH) vitamin D levels and lipid profiles in subjects with vitamin D insufficiency and those with normal lipid profiles.Materials and Methods: This study was carried out among the obese and non-obese individuals with vitamin D deficiency. Vitamin D level was estimated in all the patients. Further, the lipid profiles, Homeostatic Model Assessment HOMA and bone density (T and Z scores) were measured in all the patients.Results: The obese subjects displayed significant increase in the BMI, VSF and TBF in as compared to the non-obese subjects. Further, the T and Z scores, Insulin, HOMA-IR, AST and ALT levels was increased in obese subjects when compared to non-obese subjects and found to be significant. In addition, there was significant negative correlation between VLDL and triglycerides in vitamin D deficiency subjects.Conclusion: Thus the present study, confirm that there was marked alteration in lipid profiles in subjects with vitamin D deficiency.